Assessing Digital Innovation and Sustainable Entrepreneurship among Business Owners and Managers in Southwest Nigeria - BANKOLE , Oluseun Ayodele (Covenant Journal of Entrepreneurship, 2024)
This study investigates the relationship between digital innovation and sustainable entrepreneurial performance among business owners and managers in Southwest Nigeria. The problem statement arises from the imperative to understand how digital innovation influences regional businesses' long-term success and viability. The study aims to assess the impact of digital innovation strategies, including technology adoption, skills development, and access to infrastructure, on sustainable entrepreneurial performance. Methodologically, a questionnaire administered via Google Forms was utilized to collect data from a purposive sample of 238 business owners and managers. The analysis employed measurement and structural models to examine the relationships between digital innovation variables and entrepreneurial outcomes. The findings reveal significant positive relationships between digital technology adoption, skills development, access to infrastructure, and sustainable entrepreneurial performance. Implications for business managers include the importance of investing in digital readiness initiatives, fostering a culture of innovation, and leveraging strategic partnerships to drive sustainable growth and competitiveness. Managerial recommendations include prioritizing investments in digital infrastructure, implementing supportive regulatory frameworks, and fostering continuous learning and innovation within organizations.